The effects of increased exposure time to UV-B radiation on germination and seedling development of Anatolian black pine seeds - Ozel, Halil Baris; Abo Aisha, Adel Easa Saad; Cetin, Mehmet; Sevik, Hakan; Zeren Cetin, Ilknur (Springer Science and Business Media LLC, 2021)
Exhaustion of stratospheric ozone found at a height of 10-30 km around the world causes the solar UV-B (280-320 nm) radiation to penetrate through the atmosphere more, and thus to reach the Earth's surface quicker. The protective ozone layer gets damaged by human activities constantly, and the increasing levels of UV radiation present threats to all life forms, plants, animals, and even microorganisms. However, the studies conducted on the effects of UV radiation on plants, and especially forest trees, are rather limited. In this study, it was aimed to identify the effects of UV-B radiation on some germination and seedling characteristics of Anatolian black pine seeds. Within the scope of the study, seeds were exposed to UV-B radiation for 5, 10, 20, 30, 40, 50, and 60 min for germination experiments; and the germination speed (GS) was calculated as the ratio of the germinated seeds to the solid seeds at the end of the 7th day, whereas the germination percentage (GP) was calculated as the ratio of the germinated seeds to the solid seeds at the end of the 35th day. The seeds reserved for the seedling experiment were exposed to UV-B radiation for 1, 3, 5, and 7 h. With the measurements made at the end of the day, the seedling length (SL), the terminal bud length (TBL), the branch number (BN), the root collar diameter (RCD), the stem fresh weight (SFW), the root fresh weight (RFW), the stem dry weight (SDW) and the root dry weight (RDW), and the rooting percentage (RP) were determined. Variance analysis and Duncan test were applied to the obtained data with the help of SPSS package program. The study results revealed that the exposure time to increased UV-B radiation significantly affected all characters; the least affected character was RP, and that the most affected characters were RDW, SDW, and RCD. As a result of the study, it was found that even the applications with the lowest intensity took effect in most of the characters, that the seedling development decreased by more than 80% in terms of some characters at the end of 7-h application, and that even the decrease in the RP character, which was the least affected by the 7-h UV-B application, was above 50%.
Keywords: Uv-B Application; Pinus Nigra Arnold; Radiation; Ultraviolet Rays; Morphological Characters; Germination; Growth; Management, Monitoring, Policy and Law; Seedlings; Germination Speed; Seeds; Rooting Percentage; Environmental Monitoring; 2. Zero hunger; 15. Life on land; 13. Climate action